Roh Antikristus sebagai Kuasa Impersonal dalam Surat-Surat Yohanes dan Tantangannya bagi Spiritualitas Zaman Baru - Lucky Richard Sariowan (Sekolah Tinggi Teologi Kanaan Nusantara, 2026)
The New Age Movement (NZM) is a modern 20th-century spiritual phenomenon that emphasizes the divinity of the universe and that humans are part of the